ERCP - Law, Ryan; Baron, Todd H. (Endoscopy, 2013)
Technological advances in ERCP have appeared to plateau. Nonetheless, specific areas within ERCP were well represented at this year’s Digestive Disease Week (DDW). These areas are subdivided and discussed in detail. As expected, there remains concern about prevention of post-ERCP pancreatitis (PEP). Although pharmacologic therapy by using nonsteroidal anti-inflammatory drugs (NSAIDs) has clearly emerged as an alternative and/or adjunct to pancreatic duct (PD) stents, stents seem to remain the mainstay in the endoscopists’ armamentarium for the prevention of PEP. Other topics covered included the use of cholangioscopy, diagnosis of biliary strictures, and treatment of strictures by using stents and radiofrequency ablation.